BRONCHIOLITIS: THE RECENT EVIDENCE - Mustafa, Ghulam (Journal of Ayub Medical College Abbottabad, 2014)
Bronchiolitis is an active area of research across the spectrum from genetic mechanisms to population-based research. Surveillance studies are identifying new causes of bronchiolitis and exploring the role of viral co-infections. The studies have revealed that comorbidities are an important determinant to predict the course of the illness. Also the specific physical findings and diagnostic tests used to predict the outcomes in bronchiolitis do not have high predictive value. The pulse oximetry, probably, is a double edge sword. It has contributed to better childcare but is also likely contributing to longer hospitalizations and greater use of health care resources. The available data is yet largely against the routine use of bronchodilators or corticosteroids, though a combination of these two looks promising future trend. The role of nebulized hypertonic saline in bronchiolitis is getting a wider acceptance and is likely to get established a part of routine care. Keywords: Bronchiolitis, Bronchodilators, Corticosteroids, Nebulized hypertonic saline